Strobelitatea, a replacement name for Strobeliella Cazzaniga, 1981 (Gastropoda: Tateidae), non Nordsieck, 1977 (Gastropoda: Clausiliidae) - Cazzaniga, Néstor J. (Zootaxa, 2017)
When I proposed the name Strobeliella for a genus of supposedly microphallic snails in the family Hydrobiidae, I was unaware that it was a junior homonym of Clausilia (Strobeliella) published four years before by Nordsieck (1977).